Paving the Delaware Way: Legislative and Equitable Limits On Bylaws After ATP - Michael J. Kaufman; John M. Wunderlich (Washington University Law Review, 2015)
In ATP Tour, Inc. v. Deutscher Tennis Bund, the Delaware Supreme Court held that a private company’s fee-shifting bylaw was facially valid. And before that decision, Delaware courts similarly upheld companies’ use of forum-selection bylaws requiring that intra-corporate disputes be litigated in a single designated forum. Many interpreted these holdings as broad endoresements of bylaws that could regulate the litigation process itself and a move by the Delaware courts to curtail shareholder litigation. Indeed, the Delaware legislature itself responded to ATP, amending the state’s corporate law to explicitly prohibit Delaware companies from adopting fee-shifting bylaws for shareholder litigation. But the legislature simultaneously allowed Delaware companies to adopt forum-selection bylaws. In this Article, we show that ATP and caselaw related to forum-selection bylaws will not result in calamity for investors or provide a silver bullet for companies to end shareholder and securities litigation. Rather, when carefully and fairly read, these decisions simply reaffirm the Delaware Way, under which corporate managers are vested with broad legal authority, but that authority is tempered by principles of equity. Using ATP and fee-shifting bylaws as a point of departure, we provide a template for equitable analysis of not only fee-shifting bylaws, but also forum-selection bylaws and other bylaws relating to litigation. Furthermore, as we argue in this Article, had equitable principles been properly applied to fee-shifting bylaws, equitable principles would have likely prevented fee-shifting bylaws from extinguishing meritorious shareholder or securities litigation anyway. In fact, the only kind of fee-shifting bylaw that would likely have survived equitable scrutiny is one that already exists under Delaware’s Rule 11—one that provides that a neutral arbiter can approve of two-way shifting of reasonable fees in response to frivolous litigation. Ultimately, perhaps the most compelling case for legislation barring fee-shifting bylaws in other states that follow the Delaware Way is that doing so may spare litigants and the system the lengthy, common-law process that will likely arrive at the state of the law already in place. In ATP Tour, Inc. v. Deutscher Tennis Bund, the Delaware Supreme Court held that a private company’s fee-shifting bylaw was facially valid. And before that decision, Delaware courts similarly upheld companies’ use of forum-selection bylaws requiring that intra-corporate disputes be litigated in a single designated forum. Many interpreted these holdings as broad endoresements of bylaws that could regulate the litigation process itself and a move by the Delaware courts to curtail shareholder litigation. Indeed, the Delaware legislature itself responded to ATP, amending the state’s corporate law to explicitly prohibit Delaware companies from adopting fee-shifting bylaws for shareholder litigation. But the legislature simultaneously allowed Delaware companies to adopt forum-selection bylaws. In this Article, we show that ATP and caselaw related to forum-selection bylaws will not result in calamity for investors or provide a silver bullet for companies to end shareholder and securities litigation. Rather, when carefully and fairly read, these decisions simply reaffirm the Delaware Way, under which corporate managers are vested with broad legal authority, but that authority is tempered by principles of equity. Using ATP and fee-shifting bylaws as a point of departure, we provide a template for equitable analysis of not only fee-shifting bylaws, but also forum-selection bylaws and other bylaws relating to litigation. Furthermore, as we argue in this Article, had equitable principles been properly applied to fee-shifting bylaws, equitable principles would have likely prevented fee-shifting bylaws from extinguishing meritorious shareholder or securities litigation anyway. In fact, the only kind of fee-shifting bylaw that would likely have survived equitable scrutiny is one that already exists under Delaware’s Rule 11—one that provides that a neutral arbiter can approve of two-way shifting of reasonable fees in response to frivolous litigation. Ultimately, perhaps the most compelling case for legislation barring fee-shifting bylaws in other states that follow the Delaware Way is that doing so may spare litigants and the system the lengthy, common-law process that will likely arrive at the state of the law already in place.
Keywords: Delaware; Corporate Law; Fees; Fee-shifting; ATP Tour; Inc. v. Deutscher Tennis Bund; Shareholder suit; Shareholder litigation